Effect of Contour Bunding on Production and Productivity of Important Cereals and Cash Crops in Maharashtra State - Kulkarni, G.A.; Raheja, S.K. (Journal of Soil and Water Conservation, 2022)
In the context of low level of agricultural production in the country, various efforts like fertilizer application, irrigation growing high yielding varieties etc. are being made to raise it for achieving self-sufficiency in food. However, the irrigated area in the country is only of the order of 27.3% of the total cultivated area at present and can be increased at the most to about 50%. It is essential, therefore, that the remaining area which cannot be provided with irrigation is covered by soil and moisture conservation measures like contour bunding and dry farming practices, etc. Maharashtra State is one of the major States growing a variety of cereal crops and a very large proportion of its cultivated area is unirrigated.